The Evolution of the Industrial Specialization of the Radio Electronics Industry of Saint-Petersburg - D. V. Klushantsev (Модернизация, инновация, развитие)
Purpose: to reveal possible directions of the development of the radio electronics industry of Saint-Petersburg on the basis of the research of its features, and to propose economically reasonable alternative in relation to the current situation.Methods: the article is based on the analysis of modern literature on the development of Russian mechanical engineering, in particular the radio electronics industry, processing of annual financial statements of enterprises of the radio electronics industry of St. Petersburg for the period 2013–2017. The article uses the following methods: analysis, synthesis, grouping, comparison, observation, generalization.Results: the literature devoted to the radio electronics industry, its transformation and development is critically analyzed. It is concluded that there are only theoretical developments and it is necessary to research the dynamics of cost indicators and qualitative transformations of the production activity of enterprises. The scheme of composition of radio electronics industry products in relation to production processes is presented. Data sources for the enterprises of the radio electronics industry are described. The author presents a sample of enterprises.To obtain the results of the study, the following feature of the radio electronics industry in Saint Petersburg is highlighted: the concentration of many manufacturers of various products with almost identical production processes. Various scenarios of development of the explored enterprises are described.On the basis of research of coefficients of input of the equipment and sales growth for the period of 2013–2017 we grouped the enterprises. We revealed, that the greatest economic effect from optimizing the organization of production activity can be achieved in medium-sized enterprises.A way of the most effective use of the current situation in the industry is proposed, which consists in creating a software platform that unites the production equipment of enterprises of the radio electronics industry. The prerequisites for the implementation and usage of the proposed software platform are researched.Conclusions and Relevance: the author propose the option of the most efficient use of the existing situation in the modern industry (nonoptimal distribution of the equipment). The option consists in creating a software platform that will unite all the production equipment of the enterprises in the information network for the purpose of optimization of the machine utilization. This suggestion matches the trends of modern scientific researches and may be carried out by using modern digital technologies. The proposed recommendations and results are reasonable to use in the development of the state industrial policy and in designing a strategy for the production by the enterprises.